PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN Studi MASYARAKAT NELAYAN DI DESA SONI KABUPATEN TOLI-TOLI - Daniel T.todapa; Juemi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the form of participation of fishing communities in development, as well as determine the factors that encourage and inhibit community participation, and the efforts made by the government to increase community participation in planning and implementing development. This research method uses qualitative methods, with a descriptive type , data sources are primary data and secondary data, data collection techniques are carried out using interview observation and documentation techniques. There were 6 informants in this study. The data analysis used data analysis by Miles Huberman and Saldana. From the results of the research conducted, from Pasaribu & Simanjuntak's theory in Huraerah which consists of five indicators, it was found that two aspects were quite good, namely property participation and social participation. It can be seen from the enthusiasm of the community in donating funds, food, or equipment that can be used in implementing development. The other three aspects, namely participation in ideas, participation in energy, and participation in skills and abilities, are not yet good because the community is still apathetic about development, they are only busy with fulfilling their daily needs, and lack self-awareness to be involved in implementing development in the village. Soni, Toli-Toli Regency.